DIABETIC FOOT INFECTIONS AND THEIR MANAGEMENT IN A TERTIARY CARE HOSPITAL - Aamir, Azizul Hasan; Nasir, Ahmed; Jadoon, Mohammad Zahid; Mehmood, Khalid; Ali, Sobia Sabir (Journal of Ayub Medical College Abbottabad, 2011)
Background: Diabetic foot is a common complication of diabetes world over. We conducted this study to determine common microbiological pathogens in Diabetic Foot Infections (DFI) at a tertiary care hospital and their management. Methods: In this observational study deep wound swabs of all admitted diabetic patients were taken, pathogens isolated, antibiotic used and its response depending on complete resolution of symptoms and biochemical markers were recorded. Data were analysed on SPSS-11. Results: A total of 114 cases were recorded. Sixty-eight (59%) cases had ulcers on forefoot, 28 (25%) mid-foot and 18 (16%) hind-foot. One hundred and four pathogens were isolated from wound swabs after debridement. Commonest pathogen isolated was Staphylococcus aureus (52, 46%) followed by E. coli (11, 10%), MRSA was found in 10 (9%) cases, streptococcus in 6 (5%) and pseudomonas in 5 (4%) cases. Polymicrobial infection was also seen in a few cases. Surgical intervention included superficial debridement in 88 (77%) cases, toe amputation/forefoot amputation in 19 (17%) cases, and below/above knee (major) amputation in 7 (6%) cases. Commonest antibiotic used was Cefoperazone/Sulbactam in 43 (38%) cases, alone or in combination, followed by Ceftraixone 36 (33%) cases. Linezolid was used for MRSA. Ninety-four (82%) patients responded to treatment and were recorded as '˜cured'. Conclusion: Diabetic Foot ulcers often present with serious foot infections. Commonest pathogens are Staph. aureus, E. coli, Pseudomonas spp. and MRSA. Treatment was effective with Cefoperazone/Sulbactam and Ceftraixone. MRSA was treated successfully with Linezolid. Keywords: Diabetic foot, Diabetic foot infections (DFI), Staph. Aureus, E. coli, MRSA, antibiotics